Final report. FLD grant September 1986-September 1987 to Federal Livestock Department of the Federal Military Government of Nigeria - International Livestock Centre for Africa (International Livestock Centre for Africa, 1988)
Presents results of a study conducted to quantify the productivity of Leucaena leucocephala and Gliricidia sepium planted in alternate raws 4 m apart and the effects of using foliage from the trees as green manure on soil fertility, and crop production and as feed for sheep and goat production. Also investigates labour requirements so that cost benefit analysis of alley farming could be undertaken. Trials were designed by the researchers and implemented on farmers' fields, in some cases being managed by the farmers. The purpose of the grant award to ILCA by the Federal Livestock Department was to continue village studies in the area of Oyo State where a pilot study was established in 1984.